Increasing Quantity and Internal Quality of Japanese Quail (Coturnix coturnix japonica) Eggs by Shooting Laser Puncture at Reproductive Acupuncture Points - Sunaryo Hadi Warsito; Tatang Santanu Adikara; Septiana Megasari; Ilham Radifan Pratama; Mirni Lamid; Herry Agoes Hermadi (Veterinary Medicine International)
This study aims to determine the effect of laser puncture shooting on the reproductive acupuncture points of Japanese quail (Coturnix coturnix japonica) egg quantity (egg production) and internal egg quality (Haugh unit, yolk index, and yolk colour). This research was conducted for 30 days using a sample of Japanese quail aged 4 weeks because for the first 2 weeks, the quail did not produce and it was in production in the last 2 weeks. There were 4 treatments and 25 replications each. So, there were a total of 100 quails. Laser puncture shooting was carried out at 3-day intervals at the Ova point and 6-day intervals at Hu Men, Bei Ji, and Wei Gen points. So, on the first day, laser puncture shooting was carried out at 4 points, on the 4th day, only at 1 point, and then, on the 7th day, it returned to 4 points. And so, it was carried out for 4 weeks. T0 (−) was considered as a negative control because quails are not given laser puncture shooting; T0 (+) was considered as a positive control because quails are treated with laser puncture shooting which is deactivated or a dose of 0 Joule; T1 was a group treated with laser puncture shooting at a dose of 0.2 Joule, and T2 was a group treated with laser puncture shooting at a dose of 0.5 Joule. Then, the research results were analyzed using Analysis of Variance and followed by Duncan’s Multiple Range Test. Laser puncture shooting at the reproductive acupuncture point of Japanese quail (Coturnix coturnix japonica) can increase the quantity of eggs (p<0.05). While the results of the egg internal quality in the form of the Haugh unit value and the yolk index increased (p<0.05), the value of the yolk colour did not change compared to the control (p>0.05). Laser puncture shooting at the reproductive acupuncture point of Japanese quail (Coturnix coturnix japonica) can increase egg quantity (egg production) and internal egg quality (Haugh unit and yolk index) with the best dose of 0.5 Joule.